Current Epidemiology of Surgical Sepsis: Discordance Between Inpatient Mortality and 1-year Outcomes. Issue 3 (September 2019) - Brakenridge, Scott C.; Efron, Philip A.; Cox, Michael C.; Stortz, Julie A.; Hawkins, Russell B.; Ghita, Gabriela; Gardner, Anna; Mohr, Alicia M.; Anton, Stephen D.; Moldawer, Lyle L.; Moore, Frederick A.
Abstract : Objective: We sought to compare traditional inpatient outcomes to long-term functional outcomes and mortality of surgical intensive care unit (SICU) patients with sepsis. Summary of Background Data: As inpatient sepsis mortality declines, an increasing number of initial sepsis survivors now progress into a state of chronic critical illness (CCI) and their post-discharge outcomes are unclear. Methods: We performed a prospective, longitudinal cohort study of SICU patients with sepsis. Results: Among this recent cohort of 301 septic SICU patients, 30-day mortality was 9.6%. Only 13 (4%) patients died within 14 days, primarily of refractory multiple organ failure (62%). The majority (n = 189, 63%) exhibited a rapid recovery (RAP), whereas 99 (33%) developed CCI. CCI patients were older, with greater comorbidities, and more severe and persistent organ dysfunction than RAP patients (all P < 0.01). At 12 months, overall cohort performance status was persistently worse than presepsis baseline (WHO/Zubrod score 1.4 ± 0.08 vs 2.2 ± 0.23, P > 0.0001) and mortality was 20.9%. Of note at 12 months, the CCI cohort had persistent severely impaired performance status and a much higher mortality (41.4%) than those with RAP (4.8%) after controlling for age and comorbidity burden (Cox hazard ratio 1.27; 95% confidence interval, 1.14–1.41, P < 0.0001). Among CCI patients, independent risk factors for death by 12 months included severity of comorbidities and persistent organ dysfunction (sequential organ failure assessment ≥6) at day 14 after sepsis onset. Conclusions: There is discordance between low inpatient mortality and poor long-term outcomes after surgical sepsis, especially among older adults, increasing comorbidity burden and patients that develop CCI. This represents important information when discussing expected outcomes of surgical patients who experience a complicated clinical course owing to sepsis. Abstract : Supplemental Digital Content is available in the text